Analytical Physical Model for Organic Metal‐Electrolyte‐Semiconductor Capacitors. Issue 1 (11th November 2022) - Huetter, Larissa; Kyndiah, Adrica; Gomila, Gabriel
Abstract: This work presents the analytical physical modeling of undoped organic metal‐electrolyte‐semiconductor (OMES) capacitors in the framework of the Nernst–Planck–Poisson theory, including the presence of compact interfacial layers. This work derives an exact analytical solution, up to a quadrature, for the stationary electric potential and charge density distributions in both the semiconductor film and the electrolyte solution, and from them the sheet semiconductor charge and the stationary differential capacitance are obtained as a function of the applied voltage. The dependence of these magnitudes on the physical device parameters, like the ionic concentration of the electrolyte, the capacitance of the interfacial compact layers and the injected hole density is then analyzed. This work shows that ionic diffusive effects in the electrolyte can play an important role in the device response, inducing a broadening of the transition from the weak to the strong accumulation regimes. This fact can make that the strong accumulation regime is not achieved in OMES within the usual voltage operation range of these devices. The analytical solution is validated by means of finite element numerical calculations. The implications of the results obtained on the physics of electrolyte gated organic field effect transistors (EGOFETs) are discussed. Abstract : An analytical physical model for the capacitance of organic metal‐electrolyte‐semiconductor capacitors is obtained by solving the drift–diffusion model for the semiconductor coupled to the Nernst–Planck–Poisson model for the electrolyte, including the presence of compact interfacial Stern layers. Results show that ionic diffusive effects in the electrolyte can play a significant role.